2019
DOI: 10.2147/ijn.s223318
|View full text |Cite
|
Sign up to set email alerts
|

<p>ZnO Nanoparticles Induced Male Reproductive Toxicity Based on the Effects on the Endoplasmic Reticulum Stress Signaling Pathway</p>

Abstract: PurposeThe aim of this study was to evaluate the adverse effects of ZnO NPs on male reproductive system and explore the possible mechanism.MethodsIn this study, the effect of oral administration of 50, 150 and 450 mg/kg zinc oxide nanoparticles (ZnO NPs) in adult male mice was studied over a 14-day period.ResultsThe results showed that the number of sperms in the epididymis and the concentration of testosterone in serum were decreased with an increased dose of ZnO NPs. Testicular histopathological lesions like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 55 publications
(53 reference statements)
5
51
0
Order By: Relevance
“…Interestingly, Hussein et al, 2016 revealed that these changes in sperm quality could be alleviated by co-exposure with quercetin, a potent antioxidant. The number of Leydig cells also decreases after exposure to a low concentration of ZnO NPs, and as a consequence, serum testosterone levels decrease, as reported in Wistar Han rats [78] and Kunming mice [75,86]. Additionally, the same authors explored the influence of ZnO NPs on steroidogenesis enzymes by assessing the mRNA levels of steroidogenic proteins in testis samples, namely 3β-hydroxysteroid dehydrogenase (3β-HSD), 17β-hydroxysteroid dehydrogenases (17β-HSD), and steroidogenic factor 1 (Nr5A1) [78].…”
Section: In Vivo Studiessupporting
confidence: 57%
See 4 more Smart Citations
“…Interestingly, Hussein et al, 2016 revealed that these changes in sperm quality could be alleviated by co-exposure with quercetin, a potent antioxidant. The number of Leydig cells also decreases after exposure to a low concentration of ZnO NPs, and as a consequence, serum testosterone levels decrease, as reported in Wistar Han rats [78] and Kunming mice [75,86]. Additionally, the same authors explored the influence of ZnO NPs on steroidogenesis enzymes by assessing the mRNA levels of steroidogenic proteins in testis samples, namely 3β-hydroxysteroid dehydrogenase (3β-HSD), 17β-hydroxysteroid dehydrogenases (17β-HSD), and steroidogenic factor 1 (Nr5A1) [78].…”
Section: In Vivo Studiessupporting
confidence: 57%
“…Most of the in vivo studies reported in Table 2 evaluate changes in testicular and epididymal tissues after exposure of rats or mice to different ZnO NPs concentrations. The histological pattern was similar in both rats or mice, with the formation of multinucleated giant cells [76,77], disorganization of germ cells layers, detachment and sloughing of immature germ cells, and vacuolization of the epithelium of ST after exposure to a high concentrations of ZnO NPs [75][76][77][78]80,86]. These histological alterations are indicative of functional damage in Sertoli cells, which are responsible for the support and protection of germ cells during spermatogenesis [76].…”
Section: In Vivo Studiesmentioning
confidence: 89%
See 3 more Smart Citations